Cover Crops and Corn Residue Removal: Impacts on Soil Hydraulic Properties and Their Relationships with Carbon. Issue 1 (1st February 2019) - Sindelar, Michael; Blanco-Canqui, Humberto; Jin, Virginia L.; Ferguson, Richard
Abstract : Core Ideas: Cover crop generally had no effect on water infiltration, water retention, and available water after 5 and 6 yr. Corn residue removal reduced water infiltration, water retention, and available water after 5 and 6 yr. Cover crop partially mitigated the negative impacts of corn residue removal on soil hydraulic properties. Reductions in soil micropores and soil C concentration due to corn residue removal partly explained the reduction in plant‐available water. Large‐scale crop residue removal may negatively affect soil water dynamics. Integrating cover crop (CC) with crop residue management can be a strategy to offset potential adverse effects of residue removal. We studied: (i) the impact of corn ( Zea mays L.) residue removal (56%) with and without the use of winter rye ( Secale cereale L.) CC on soil hydraulic properties, (ii) whether CC would ameliorate residue removal effects on hydraulic properties, and (iii) relationships of hydraulic properties with soil organic C (SOC) and other properties under irrigated no‐till continuous corn on a silt loam in south central Nebraska after 5 and 6 yr of management. Cover crops did not affect soil hydraulic properties. However, residue removal reduced cumulative water infiltration by about 45% in one year. Across years, residue removal reduced plant available water (PAW) by 32% and mean weight diameter of water‐stable aggregates (MWD) by 23% for the upper 5‐cm soil depth. Under no CC, residue removal reduced SOC concentration by 25% in the 0‐ to 5‐cm and by 11% in the 5‐ to 10‐cm depths. Under residue removal, CC increased SOC concentration by 18% in the 0‐ to 5‐cm and by 8% in the 5 to 10‐cm depths. Cover crop did not completely offset the residue removal‐induced decrease in SOC concentration in the upper 5‐cm depth. Plant available water decreased as SOC concentration and MWD decreased. After 6 yr, corn residue removal adversely affected soil hydraulic properties and SOC concentration, but CC was unable to fully offset such adverse impacts.